Mito y ciencia ficción: una aproximación a la obra de Santiago Páez [Dossier Literatura Ecuatoriana (Siglos XX-XXI): otros desciframientos (Ponencias presentadas en el Congreso de la Asociación de Ecuatorianistas, Quito, 20-21 de julio de 2015)] - Ormaza Lizarzaburu, Jessica (2016)
From the analysis of the novel De shamanes y reyes by the Ecuadorian writer Santiago Páez, the interrelation between apparently contradictory universes is evident: archetypal characters coming from a society with mythical thought that act and dialogue in a futuristic context; and the coexistence of these universes, in principle opposites, such as that of science and that of ancestral traditions and wisdoms, which is possible thanks to the presence of a mythical conception of the world, of the beings that inhabit it and of the passing of time. In other words, the coexistence of these universes is possible thanks to a shared symbolic reading of the phenomena of the universe.